Crossing Potential of Open Pollination in Cajuputi Seedling Seed Orchard at Paliyan, Gunungkidul - Noor Khomsah Kartikawati; Sumardi (Foresty Faculty of Hasanuddin University, 2017)
There are two possibilities on open pollination: cross pollination and self pollination. This research was aimed to identify cross pollination potential within and among provenance, and to determine the flowering behavior of each provenance in seedling seed orchard of cajuputi at Paliyan, Gunungkidul. The research was conducted based on flowering phenology (start of flowering, end of flowering and duration of flowering in one period) for all flowering trees during two flowering periods. The result showed that there was high crossing potential in seedling seed orchard of cajuputi based on flowering synchrony. Land race of Gundih has highest crossing potential due to longevity and intensity of flowering, while the provenance from Northern Australia has the lowest crossing potential. Other provenances (Masarete, Rat Gelombeng, Waipirit, Pelita Jaya, Cotonea, Suli and Western Australia) also have high crossing potential at the time when the number of individual was greatest and flowering intensity highest. This research demonstrated that high crossing potential was found within provenance and among provenances except Northern Australia. The implication of this research deployment of improved seed produced from open pollination in seedling seed orchard was recommended for high crossing potential expressed from flowering synchrony.